2018
DOI: 10.1002/1878-0261.12163
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fucosylation in human invasive ductal carcinoma reduces E‐selectin ligand expression, cell proliferation, and ERK1/2 and p38 MAPK activation

Abstract: Breast cancer tissue overexpresses fucosylated glycans, such as sialyl‐Lewis X/A (sLeX /A), and α‐1,3/4‐fucosyltransferases (FUTs) in relation to increased disease progression and metastasis. These glycans in tumor circulating cells mediate binding to vascular E‐selectin, initiating tumor extravasation. However, their role in breast carcinogenesis is still unknown. Here, we aimed to define the contribution of the fucosylated structures, including sLeX /A, to cell adhesion, cell signaling, and cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…FUT5 is a gene involved in the fucosylation of glycans in circulating tumor cells leading to the initiation of tumor extravasation. Inhibition of fucosylation has been shown to reduce oncogenic properties of breast cancer; therefore, hypomethylation and subsequent activation of FUT5 to increase fucosylation could exacerbate oncogenic properties 65 .…”
Section: Resultsmentioning
confidence: 99%
“…FUT5 is a gene involved in the fucosylation of glycans in circulating tumor cells leading to the initiation of tumor extravasation. Inhibition of fucosylation has been shown to reduce oncogenic properties of breast cancer; therefore, hypomethylation and subsequent activation of FUT5 to increase fucosylation could exacerbate oncogenic properties 65 .…”
Section: Resultsmentioning
confidence: 99%
“…IGF1R is a protein and transmembrane tyrosine protein receptor which is involved in the IGF1/MAPK signalling pathway [48,49]. P38MAPK, an important member of the MAPK signalling pathway, can activate the MAPK signalling pathway [50][51][52][53], causing the proliferation of cells [54][55][56]. Moreover, our previous studies have shown that p38MAPK signalling is inhibited by miR-451 in early DN [15].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of an α‐1,3/4‐linkage to N ‐acetylglucosamine (GlcNAc) in Gal‐GlcNAc is mediated by FUT3‐7 and FUT9‐11. FUT8 catalyzes the innermost asparagine‐linked (core) GlcNAc in N‐glycans . FUT4 catalyzes the α‐1,3 fucose linkage in Lewis x and Lewis y structures, which is associated with tumor proliferation, invasion, and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…FUT8 catalyzes the innermost asparagine‐linked (core) GlcNAc in N‐glycans . FUT4 catalyzes the α‐1,3 fucose linkage in Lewis x and Lewis y structures, which is associated with tumor proliferation, invasion, and metastasis . Increased FUT4 levels have been reported in multiple cancers, including acute myeloid leukemia, colon, and gastric and lung cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation